Efficacy and safety of regorafenib in patients with metastatic or locally advanced chondrosarcoma: Results of a non-comparative, randomised, double-blind, placebo controlled, multicentre phase II study. (June 2021) - Duffaud, Florence; Italiano, Antoine; Bompas, Emannuelle; Rios, Maria; Penel, Nicolas; Mir, Olivier; Piperno-Neumann, Sophie; Chevreau, Christine; Delcambre, Corinne; Bertucci, François; Boudou-Rouquette, Pascaline; Cancel, Mathilde; et al.
Abstract: Background: This multi-cohort trial explored the efficacy and safety of regorafenib for patients with advanced sarcomas of bone origin; this report details the cohort of patients with metastatic or locally advanced chondrosarcoma (CS), progressing after prior chemotherapy. Patients and methods: Patients with CS, progressing despite prior standard therapy, were randomised (2:1) to receive regorafenib or placebo. Patients on placebo could crossover to receive regorafenib after centrally confirmed progressive disease. The primary endpoint was progression-free rate (PFR) at 12 weeks. With one-sided α of 0.05, and 80% power, at least 16/24 progression-free patients at 12 weeks were needed for success (P0 = 50%, P1 = 75%). Results: From September 2014 to February 2019, 46 patients were included in the CS cohort, and 40 patients were evaluable for efficacy: 16 on placebo and 24 on regorafenib. Thirteen patients (54.2%; 95% CI [35.8%-[) were non-progressive at 12 weeks on regorafenib versus 5 (31.3%; 95% CI [13.2%-[);) on placebo. Median PFS was 19.9 weeks on regorafenib, and 8.0 on placebo. Fourteen placebo patients crossed over to regorafenib after progression. The most common grade ≥3 treatment-related adverse events on regorafenib included hypertension (12%), asthenia (8%), thrombocytopenia (8%) and diarrhoea (8%). One episode of fatal liver dysfunction occurred on regorafenib. Conclusion: Although the primary endpoint was not met statistically in this small randomised cohort, there is modest evidence to suggest that regorafenib might slow disease progression in patients with metastatic CS after the failure of prior chemotherapy. Clinical trial registration: The trial is registered at ClinicalTrials.gov (NCT02389244 ). Highlights: Progression-free rate at 12 weeks was 54% on regorafenib and 31% on placebo. Median PFS was 19.9 weeks on regorafenib, and 8.0 weeks on placebo. PFS rate at 24 weeks was 43% for patients on regorafenib and 25% on placebo. The safety of regorafenib was as expected despite one fatal case of hepatic toxicity. These results suggest modest activity of regorafenib in metastatic chondrosarcoma.